2015
DOI: 10.1063/1.4921286
|View full text |Cite
|
Sign up to set email alerts
|

Electric properties and carrier multiplication in breakdown sites in multi-crystalline silicon solar cells

Abstract: This paper studies the effective electrical size and carrier multiplication of breakdown sites in multi-crystalline silicon solar cells. The local series resistance limits the current of each breakdown site and is thereby linearizing the current-voltage characteristic. This fact allows the estimation of the effective electrical diameters to be as low as 100 nm. Using a laser beam induced current (LBIC) measurement with a high spatial resolution, we find carrier multiplication factors on the order of 30 (Zener-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Among various types of shunts, those associated with local breakdown of solar cells under reverse bias can be mentioned [5][6][7][8][9]. It was shown that such breakdown sites can be revealed by reverse-bias electroluminescence (EL) [5][6][7][8][9][10] and their classification was carried out [6,11]. The correlation of EL images with those obtained by the electron beam induced current (EBIC) method sometimes allows finding a link between these sites and extended defects [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various types of shunts, those associated with local breakdown of solar cells under reverse bias can be mentioned [5][6][7][8][9]. It was shown that such breakdown sites can be revealed by reverse-bias electroluminescence (EL) [5][6][7][8][9][10] and their classification was carried out [6,11]. The correlation of EL images with those obtained by the electron beam induced current (EBIC) method sometimes allows finding a link between these sites and extended defects [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this misunderstanding is determined by the manifold nature of shunts, especially in multicrystalline Si, and by a variety of extended defects and impurities in this material. Among various types of shunts, those associated with local breakdown of solar cells under reverse bias can be mentioned [5][6][7][8][9]. It was shown that such breakdown sites can be revealed by reverse-bias electroluminescence (EL) [5][6][7][8][9][10] and their classification was carried out [6,11].…”
Section: Introductionmentioning
confidence: 99%